THE ROLE OF INFLAMMATORY RESPONSE AND ANTIOXIDANT PROTECTION MARKERS IN THE PATHOGENESIS OF ABDOMENALGIA IN PATIENTS WITH CHRONIC PANCREATITIS COMORBID WITH HYPERTENSIVE DISEASE - Arkhiy, E.Y.; Prylypko, L.B.; Horlenko, O.M.; Moskal, O.M. (World of Medicine and Biology, 2020)
Modern medicine is gradually losing the mononosological nature of the disease course, and the trend towards polymorbidity is becoming more and more noticeable. The combination of multi-organ changes has a negative effect on the clinical course of all diseases. A frequent common combination in clinical practice is a combination of chronic pancreatitis and hypertension. The purpose of our study was to determine the effect of laboratory parameters of the antioxidant defense system and markers of inflammatory response on the intensity of abdomenalgia in patients with chronic pancreatitis comorbid with hypertension disease. The results of our study are complementary to the fundamental knowledge on the pathogenesis of combined pathology, namely the element of a subjective parameter formation - abdomenalgia. It has been proven that leukocytes, ESR, α1-antitrypsin, glutathione peroxidase, selenium and zinc are key parameters in the formation of abdominal pain. Based on these laboratory parameters activity level, it is recommended to expand the basic set of medical measures in order to accelerate removing of abdomenalgia.